2006
DOI: 10.1136/hrt.2007.117309
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of femoral versus radial approach for percutaneous coronary intervention using abciximab in acute myocardial infarction: results of the FARMI Trial

Abstract: Objective: To compare bleeding complications and results of percutaneous coronary intervention (PCI) between patients treated by radial and femoral approaches for acute myocardial infarction (AMI,) and using abciximab and 5 French guiding-catheters. Patients: 114 consecutive patients with AMI were prospectively randomised. Exclusion criteria were a history of coronary artery bypass graft, cardiogenic shock, atrioventricular block, and contraindication to abciximab or a negative Allen test. Local haemostasis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 27 publications
6
57
0
1
Order By: Relevance
“…It included 114 patients presenting with acute myocardial infarction with a negative Allen's test and not in cardiogenic shock. The study found lower peripheral arterial complications with earlier deambulation in the TRA group, despite a slightly higher crossover rate and angiography and fluoroscopy time, with similar PCI duration and length of hospital stay [30]. In addition, in older adults (> 70 years of age) with acute myocardial infarction, TRA showed similar success with similar door-to-balloon time (except for the small percentage of patients in which crossover was necessary) and significantly fewer vascular complications [31].…”
Section: Meta-analysesmentioning
confidence: 74%
“…It included 114 patients presenting with acute myocardial infarction with a negative Allen's test and not in cardiogenic shock. The study found lower peripheral arterial complications with earlier deambulation in the TRA group, despite a slightly higher crossover rate and angiography and fluoroscopy time, with similar PCI duration and length of hospital stay [30]. In addition, in older adults (> 70 years of age) with acute myocardial infarction, TRA showed similar success with similar door-to-balloon time (except for the small percentage of patients in which crossover was necessary) and significantly fewer vascular complications [31].…”
Section: Meta-analysesmentioning
confidence: 74%
“…Peripheral arterial disease is strongly associated with baseline anemia (1); therefore, the radial access appears particularly attractive in these patients (1). This route, initially reserved for elective patients, is increasingly used in selected patients undergoing primary angioplasty (12).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 33% of patients with ACS have creatinine clearance <60 mL/min [46]. Access via the radial artery during PCI has been shown to reduce the rate of severe bleeding, compared with femoral artery access [47,48].…”
Section: Factors Associated With Bleeding Risk Older Age Female Sexmentioning
confidence: 99%